2020
DOI: 10.1183/13993003.00652-2020
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial antiviral signaling protein is crucial for the development of pulmonary fibrosis

Abstract: Danger signals, or damage-associated molecular patterns (DAMPs), instigate mitochondrial innate immune responses wherein Mitochondrial Antiviral Signalling protein (MAVS) functions as a key platform molecule to mediate them. The role of MAVS in the pathogenesis of idiopathic pulmonary fibrosis (IPF), however, has not been identified yet. A possibility whether the MAVS signalling can be modulated by currently existing drugs has not been explored, either. Here, using an established model of pulmonary fibrosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Although several studies mentioned detrimental aspects of MAVS in acute tubular necrosis 33 and unilateral ureteral obstructions, 34 our findings revealed that systemic MAVS signaling plays a renoprotective role in DKD. The multifunction of MAVS have recently been reported in other diseases such as energy metabolism, 35 pulmonary fibrosis, 36 and colon tumor progression 37 . Notably, accumulating evidence indicates that MAVS signaling contributes to controlling and protecting intestinal permeability 21 23 …”
Section: Discussionmentioning
confidence: 99%
“…Although several studies mentioned detrimental aspects of MAVS in acute tubular necrosis 33 and unilateral ureteral obstructions, 34 our findings revealed that systemic MAVS signaling plays a renoprotective role in DKD. The multifunction of MAVS have recently been reported in other diseases such as energy metabolism, 35 pulmonary fibrosis, 36 and colon tumor progression 37 . Notably, accumulating evidence indicates that MAVS signaling contributes to controlling and protecting intestinal permeability 21 23 …”
Section: Discussionmentioning
confidence: 99%
“…As fibrotic fibroblasts employ antiapoptotic BCL-2 family proteins to stay alive through the sequestration of proapoptotic activators, their priming status shifts, allowing them to become exquisitely sensitive to the effects of BH3 mimetics ( 24 , 27 , 41 , 42 ). BCL-2 inhibition with the BH3 mimetics have demonstrated efficacy in the single-dose bleomycin model to inhibit the development of fibrosis (if given during the inflammatory phase) and hasten spontaneous resolution of fibrosis (if given during the fibrotic phase) ( 26 , 43 , 44 ). However, because single-dose bleomycin is a model of homeostatic fibrosis resolution ( 6 , 8 , 12 ), it is a suboptimal model for studying fibroblast accumulation and resistance to apoptosis in the context of nonresolving lung disease, thus prompting our use of repetitive bleomycin and silicosis as models of persistent, progressive pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…ABT-263 has recently been shown to attenuate the development of pulmonary fibrosis after single-dose bleomycin in mice ( 26 ) and to reduce dermal fibrosis in a model of bleomycin-induced scleroderma ( 27 ). A single dose of bleomycin is the most frequently used mouse model of pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The connection to innate immunity extends beyond Toll like receptors as shown by data implicating the NACHT, LLR and PYD domains-containing protein 3 (NALP3) inflammasome activation in IL-1β associated fibrosis in the bleomycin mouse model ( Gasse et al, 2009 ; Tian et al, 2017 ). Recent work links this process to the mitochondrial antiviral signaling (MAVS) pathway in mice and humans with IPF ( Kim et al, 2020 ). The inflammation may also be activated via toll-like receptor 9 (TLR9) ( Trujillo et al, 2010 ) which along with its endogenous ligand mitochondrial DNA (mtDNA) is increased in IPF ( Ryu et al, 2017 ).…”
Section: Innate Immune Ligands In Idiopathic Pulmonary Fibrosis: Pathogen Associated Molecular Patterns Vs Danger Associated Molecular Pamentioning
confidence: 99%